Pembinaan Masyarakat Menuju Kampung Peduli Iklim untuk Pencegahan Masalah Kesehatan dan Bencana di Jorong Jambu Air, Kecamatan Banuhampu, Kabupaten Agam - Putri Nilam Sari; Jennie Aprisina; Miftahul Jannah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The impact of climate change is a threat to vulnerable communities if they are unable to adapt and mitigate to this condition. The dangers that will arise due to climate change include hydrometeorological disasters such as floods, landslides, typhoons and storms. In addition, various health problems arising from the disaster such as death, injury, diarrhea and skin diseases. Jambu Air village is an area that borders directly with the city of Bukittinggi. Therefore, it has strong characteristics of a sub-urban area. Due to rapid population and infrastructure growth, and a large number of migrants live there, this area has risk of increasing environmental problems that have implications for increasing the negative impacts of climate change. Inappropriate waste disposal activities will increase the risk of flooding and diseases. This community service activity aims to increase the commitment of the leader of this village and youth to be more concerned about the risks of climate change to overcome health and disaster risks. The activity was carried out by lecture method in July 2019 that is located in Jorong Jambu Air, Banuhampu District. Speakers for this activity are climatologists from the Global Atmosphere Watch Koto Tabang (Meteorology Climatology and Geophysics Council) and academics from the environmental science. The activity generates commitments from community leaders and youth on the issue of climate change. It is expected that young people can increase the pro-environment behavior.